Elucidating the clinical characteristics of patients captured using different definitions of massive transfusion. Issue 1 (2nd April 2014) - Zatta, A. J.; McQuilten, Z. K.; Mitra, B.; Roxby, D. J.; Sinha, R.; Whitehead, S.; Dunkley, S.; Kelleher, S.; Hurn, C.; Cameron, P. A.; Isbister, J. P.; Wood, E. M.; et al.
<x xml:space="preserve">Abstract</x> Background and Objectives The type and clinical characteristics of patients identified with commonly used definitions of massive transfusion (MT) are largely unknown. The objective of this study was to define the clinical characteristics of patients meeting different definitions of MT for the purpose of patient recruitment in observational studies. Materials and Methods Data were extracted on all patients who received red blood cell (RBC) transfusions in 2010 at three tertiary Australian hospitals. MT patients were identified according to three definitions: ≥10 units RBC in 24 h (10/24 h), ≥6 units RBC in 6 h (6/6 h) and ≥5 units RBC in 4 h (5/4 h). Clinical coding data were used to assign bleeding context. Data on in‐hospital mortality were also extracted. Results Five hundred and forty‐two patients met at least one MT definition, with 236 (44%) included by all definitions. The most inclusive definition was 5/4 h (508 patients, 94%) followed by 6/6 h (455 patients, 84%) and 10/24 h (251 patients, 46%). Importantly, 40–55% of most types of critical bleeding events and 82% of all obstetric haemorrhage cases were excluded by the 10/24 h definition. Patients who met both the 5/4 h and 10/24 h definitions were transfused more RBCs (19 vs. 8 median total RBC units; P < 0·001), had longer ventilation time (120 vs. 55 h; P < 0·001), median ICU (149 vs. 99 h; P < 0·001) and hospital length of stay (23 vs. 18 h; P = 0·006) and had a higher in‐hospital mortality rate (23·3% vs. 16·4%; P = 0·050). Conclusion The 5/4 h MT definition was the most inclusive, but combination with the 10/24 h definition appeared to identify a clinically important patient cohort.